Convenient route for Au@Ti-SiO2 nanocatalyst synthesis and its application for room temperature CO oxidation - Soni, Yogita; Kumar, Anumol Erumpukuthical Ashok; Nayak, Chandrani; Deepak, Francis Leonard; Vinod, C. P. (Journal of Physical Chemistry C, 2017)
Small gold nanoparticles.of size less than 5 nm encapsulated inside titanium modified silica shell have been reported. Here, a modified sol-gel method, which is a one-step process, produces Au@Ti-SiO2 nanocatalyst with a good control of titanium loading. With a titanium loading of 0.9 and 2.2 wt % in silica, unprecedented low temperature activity (full conversion) is observed for this catalyst for CO oxidation reaction compared to Au@SiO2 catalyst. A combination of optimum sized gold nanoparticles with a large amount of oxygen vacancies created due to Ti incorporation in silica matrix is considered to be the reason for this enhanced catalytic activity. The size of.gold nanoparticles is maintained even after high temperature pretreatments, which show the benefit of encapsulation. The effect of the various pretreatments on the catalytic activity has also been reported.